FINANCIAL PLANNING COUNSELING: MANAGING POCKET MONEY AND THE IMPORTANCE OF SAVING FOR STUDENTS' FUTURE AT TRISAKTI MATARAM HIGH SCHOOL - Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Rosita (Nusadaya Journal of Multidiciplinary Studies, 2026)
Financial planning counseling for high school students is one effort to improve financial literacy from adolescence. This community service activity aims to provide Trisakti Mataram High School students with an understanding of how to manage their pocket money wisely, distinguish between needs and wants, and develop savings habits for the future. The methods used include counseling, interactive discussions, simple case studies, and evaluation through pre- and post-tests. The results of the activity indicate an increase in students' understanding of personal financial management and the importance of setting aside a portion of their pocket money for savings. This program has a positive impact on developing more responsible financial behavior, thus supporting students' future financial independence.